Distance Measurements by Fluorescence Energy Homotransfer: Evaluation in T4 Lysozyme and Correlation with Dipolar Coupling between Spin Labels - Zou, Ping (Biophysical Society, 2007)
We demonstrate the feasibility and practical limitations of using steady-state anisotropy to determine distances from fluorescence homotransfer in the context of a protein of known crystal structure. Eight double mutants of T4 lysozyme spanning the distance range between 20 Å and 50 Å were labeled with a methanethiosulfonate derivative of fluorescein. The measured distances in liquid solution are in agreement with those determined from dipolar coupling between spin labels in the frozen state. They can be interpreted in the context of the crystal structure after accounting for the probe linking arm. Overall, the results establish the necessary calibration for this spectroscopic ruler. The measurement of similar distance trends using independent probes sets the stage for the complementary use of homotransfer and dipolar coupling in the determination of static structures and detection of conformational changes.